Borrelia puertoricensis in opossums (Didelphis marsupialis) from Colombia (2023)
Background The genus Borrelia comprises pathogenic species of bacteria that pose a signifcant risk to public health. Borrelia spp. are emerging or reemerging infectious agents worldwide with complex transmission cycles, and many species use rodents as vertebrate reservoir hosts. Spirochetes morphologically compatible with Borrelia have been recurrently observed in opossums; however, there is currently a lack of genetic evidence confrming infection or sup?porting that these marsupials are hosts of Borrelia spirochetes.